Characterization of a variant in the KCNH2 gene in an Ecuadorian patient with long QT syndrome: A case report - CADENA ULLAURI, SANTIAGO ANDRE; GUEVARA RAMIREZ, ALEXANDRA PATRICIA; TAMAYO TRUJILLO, VICTOR RAFAEL; Rita Ibarra Castillo; José Luis Laso Bayas; PAZ CRUZ, ELIUS ANDRES; Ruiz Pozo Viviana A.; SIMANCAS RACINES, DANIEL ALEJANDRO; ZAMBRANO ESPINOSA, ANA KARINA (Medwave Estudios Limitada, 2025)
Long QT syndrome is a rare cardiac channelopathy characterized by prolonged QT intervals and altered T wave morphology. The etiology of long QT syndrome is multifactorial, including environmental and genetic factors. In addition, several heart diseases have been associated with the individual's ethnicity. The objective of the present case report is to describe the genetic and clinical findings of a 44-year-old Ecuadorian man who experienced recurrent episodes of syncope, prolonged QT intervals, and emergent arrhythmias. Through next-generation sequencing, genetic analysis identified a p.Val612Met variant in the KCNH2 gene, associated with long QT syndrome type 2. These findings were key in classifying the patient’s condition as life-threatening and guiding the implementation of a personalized treatment strategy.